SINONIM MUTLAK DALAM BUKU SISWA BAHASA INDONESIA KELAS X DAN XI (KURIKULUM MERDEKA) - Lisa Kusumawardani; Suhartono; Yermia Nugroho Agung Wibowo (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
Synonyms are a type of semantic meaning relationship material that functions to enrich the vocabulary. One type of synonym is an absolute synonym, namely words that have identical meanings and can replace each other in all contexts. The use of absolute synonyms is found in Indonesian language student books for classes X and XI. This research aims to describe absolute synonyms based on word class and grammatical level in Indonesian language student books for classes X and This research uses a qualitative method with a descriptive approach. The data for this research are words, phrases and sentences in students' books for class X and XI Indonesian. The objects of this research are the class X Indonesian ebook by Aulia and Gumilar in 2021 and the class The results of this research found 50 absolute synonym data in Indonesian language student books for classes X and XI. The data is classified into (1) absolute synonyms based on word classes including 19 noun data, 1 numeral data, 5 adjective data, and 2 verb data; and (2) absolute synonyms based on grammatical level including 3 word data, 18 phrase data and 2 sentence data. Thus, it can be concluded that absolute synonyms can still be found, but they tend to be fewer than other types of synonyms.